2017
DOI: 10.1111/cmi.12769
|View full text |Cite
|
Sign up to set email alerts
|

Subversion of innate immune responses byFrancisellainvolves the disruption of TRAF3 and TRAF6 signalling complexes

Abstract: The success of pathogens depends on their ability to circumvent immune defences. Francisella tularensis is one of the most infectious bacteria known. The remarkable virulence of Francisella is believed to be due to its capacity to evade or subvert the immune system, but how remains obscure. Here, we show that Francisella triggers but concomitantly inhibits the Toll-like receptor, RIG-I-like receptor, and cytoplasmic DNA pathways. Francisella subverts these pathways at least in part by inhibiting K63-linked pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…In this light, it is interesting that components of cytosolic DNA-sensing pathways are not among phosphoproteins differentially regulated between WTand ⌬dsbA-infected DCs. It was previously shown that ⌬dsbA of LVS background stimulates the higher production of IFN-␤ than its WT counterpart (70). In contrast, the expression of Ifnb1 in DCs infected by FSC200 WT and ⌬dsbA is lower than in LVS-infected DCs and virtually indistinguishable from uninfected cells.…”
Section: Discussionmentioning
confidence: 90%
“…In this light, it is interesting that components of cytosolic DNA-sensing pathways are not among phosphoproteins differentially regulated between WTand ⌬dsbA-infected DCs. It was previously shown that ⌬dsbA of LVS background stimulates the higher production of IFN-␤ than its WT counterpart (70). In contrast, the expression of Ifnb1 in DCs infected by FSC200 WT and ⌬dsbA is lower than in LVS-infected DCs and virtually indistinguishable from uninfected cells.…”
Section: Discussionmentioning
confidence: 90%
“…Following inhalation of bacteria, lung DC and alveolar macrophages are targeted by Ft for invasion and replication. Ft deploys several effective evasion strategies to counteract host immune defenses in both the extracellular space and in intracellular compartments [15][16][17]. In addition, virulent Ft can actively suppress pro-inflammatory cytokine responses by human monocytes [18].…”
Section: Introductionmentioning
confidence: 99%
“…Once in the cytosol, F. tularensis replicates robustly, eventually triggering host cell death, which contributes to bacterial release, dissemination, and infection of additional host cells (9). Early during infection, F. tularensis actively downmodulates the host's proinflammatory responses (12)(13)(14)(15)(16)(17). In addition, F. tularensis actively dampens host programmed cell death responses during infection, presumably to preserve intracellular replicative niches (18)(19)(20)(21)(22)(23)(24).…”
mentioning
confidence: 99%